NEFOPAM IN THE STRUCTURE OF PERIOPERATIVE MULTIMODAL ANALGESIA IN PATIENTS WITH LUMBAR DISC HERNIATION: PRELIMINARY RESULTS - P. G. Genov; V. Kh. Timerbayev; A. A. Grin (Неотложная медицинская помощь, 2016)
PURPOSE OF THE STUDY. To compare efficacy and safety of nefopam and paracetamol as components of the preventive multimodal anesthesia (PMA) in patients operated on for a hernia of an intervertebral disc (hID).MATERIAL AND METHODS. In 2013, 35 patients were operated on for hID. Group 1 (21) received PMA including wound infiltration by bupivacaine, ketoprofen and paracetamol. Group 2 (15) received nefopam instead of paracetamol. Intensity of postoperative pain, side effects and satisfaction of patients with anesthesia were assessed, and in 6 months later — existence and intensity of chronic pain.RESULTS. Intensity of postoperative pain, satisfaction with anesthesia, and also frequency and intensity of chronic pain didn’t differ in group 1 and 2. Occurrence of undesirable reactions was higher in group 2.CONCLUSION. In patients receiving nefopam and paracetamol as components of PMA, intensity of postoperative pain and also occurence and intensity of chronic pain don’t differ, but the patients receiving to nefopam, experience the undesirable reactions more often which do not affect satisfaction with anesthesia.